Otimização da hidrólise enzimática das ramas de batata-doce (Ipomoea batatas (l.) lam). para obtenção de etanol de segunda geração - Macêdo, Deny Alves (Universidade Federal do Tocantins, 2020)
The biodegradation of lignocellulosic materials has been the object of many studies being applied in technological processes. The technology to convert lignocellulosic biomass into fermentable sugars presents great sustainable potential for the production of second generation ethanol. Obtaining ethanol from biomass involves two steps, first consisting of the hydrolysis of polysaccharides, generating mono and disaccharides, and later involves the fermentation of monkeys and disaccharides in ethanol. Cellulose hydrolysis generates glucose and cellobiose (a glucose dimer). On the other hand, the hydrolysis of lignins and hemicellulose generates sugars and by-products (mainly HMF, furfural and acetic acid), which often inhibit microbial fermentation. This work aimed to optimize the enzymatic hydrolysis of the potato branch to obtain second generation ethanol. For the development of the experiment, a rotational central composite planning was performed, varying temperature (30 ° C, 40 ° C and 50 ° C), time (24, 48 and 72 hours) and enzymatic loading (30, 120 and 210FPU). Response variables were the concentrations of monomers (glucose, xylose and arabinose) and inhibitors (acetic acid, hydroxymethylfurfural and furfural) in the hydrolyzate. The optimal operating conditions for the experiment were defined as temperature of 30 ° C, process time of 72 hours, enzymatic loading of 30FPU, under these conditions we would have 11.97 g / L glucose, 2.29 g / L xylose. The effects of the factors caused low concentrations of furfural and HMF inhibitors without affecting the yield of the process.